The Mission to Constantinople in 968 and Liudprand of Cremona - Sutherland, Jon N. (Traditio, 1975)
Of the documents that concern the relationship between Byzantium and Western Europe in the early Middle Ages, none is more famous or more frequently read than Relatio de Legatione Constantinopolitana, Liudprand of Cremona's description of his mission to Constantinople in 968 for Otto I. Much has been learned from his vivid if acid narrative about the Byzantine court of Nicephorus II Phocas and about East-West relations in the tenth century. Over the last forty years research has reached beneath the vivid prose in search of the true significance of that mission. But since Liudprand's is the only first-hand, detailed record of an embassy to Constantinople of that era, some scholars have given it more contemporary importance than it actually had, and, by extension, they have turned Liudprand's thoughts into subtle expressions of official Western policy. The danger in these inquiries has been to divorce the mind and moods of the creator from his creation and bestow on Relatio undeserved exaltation. The problem is to keep the document in its perspective while draining every sentence of its implications.